2014
DOI: 10.1111/icad.12068
|View full text |Cite
|
Sign up to set email alerts
|

Macro‐moth families differ in their attraction to light: implications for light‐trap monitoring programmes

Abstract: Light traps are used to make inferences about local macro‐moth communities, but very little is known about the efficiency with which they attract moths from varying distances, and how this may differ among families. We released 731 marked individuals, from three of the most common and species‐rich macro‐moth families, at several distances from low‐wattage actinic light traps in open and woodland habitat. Logistic regression showed family‐specific sampling areas: erebids were attracted from up to 27 m, geometri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
107
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(114 citation statements)
references
References 37 publications
(59 reference statements)
5
107
0
2
Order By: Relevance
“…Considering that the present study showed that most behavioral activities such as locomotion and searching occur at night, to enhance pest control efficiency, it may be useful to supplement the control of sticky cards that are used during the day with a light control system at night. Although, light traps are now widely used for pest control [6, 52, 53], negative impacts on natural pest enemies remain a concern [54, 55]. Further research will be required to test such control systems to determine whether natural pest enemies, such as spiders, parasitoids, predatory mites, are also trapped leading to a decline in their populations as well as the pest.…”
Section: Discussionmentioning
confidence: 99%
“…Considering that the present study showed that most behavioral activities such as locomotion and searching occur at night, to enhance pest control efficiency, it may be useful to supplement the control of sticky cards that are used during the day with a light control system at night. Although, light traps are now widely used for pest control [6, 52, 53], negative impacts on natural pest enemies remain a concern [54, 55]. Further research will be required to test such control systems to determine whether natural pest enemies, such as spiders, parasitoids, predatory mites, are also trapped leading to a decline in their populations as well as the pest.…”
Section: Discussionmentioning
confidence: 99%
“…It has been recognised for many years that shorter wavelengths are, in general, more attractive to moths (Frank, 2006, and references therein); attractiveness appears to peak around wavelengths of 400 nm (violet light; Cowan & Gries, 2009). The degree of attraction and preferred wavelengths both vary between moth taxa (Merckx & Slade, 2014); typically, larger-bodied moths with larger eyes are more likely to be attracted to light dominated by smaller wavelengths (van Langevelde et al, 2011; Somers-Yeates et al, 2013). Variation also appears to exist between sexes; males of some species are significantly more likely to be recorded at light traps than females (Garris & Snyder, 2010), but it is not clear if this is due to stronger male attraction to lights, or males being more active and therefore more likely to move into the zone of influence of a given light (Altermatt et al, 2009).…”
Section: Established Effects Of Artificial Light On Mothsmentioning
confidence: 99%
“…23.000 individuals and ca. 380 species rich dataset, we lumped the data from the six sampling rounds for each of the 84 local sites (20 × 20 m, as light traps have relatively small attraction radii: Merckx and Slade 2014). This analysis shows that overall macro-moth species richness is locally richest at woodland sites (mean ± SE: 77.1 ± 4.2), intermediate at meadows (63.2 ± 3.8) and tall shrub (61.7 ± 5.9), and poorest at low shrub sites (51.0 ± 4.3).…”
Section: A Case Study: Farmland Abandonment In Peneda and Its Effectsmentioning
confidence: 99%